Competence to Make Treatment Decisions in Anorexia Nervosa: Thinking Processes and Values - Jacinta Tan (Philosophy, Psychiatry, & Psychology, 2006)
This paper explores in greater depth the ethical implications of a research study on competence to make treatment decisions and how it is affected by anorexia nervosa. The issues identified involved difficulty with though processing and changes in values due to the disorder.